Analysis of microleakage at fixing the fiberglass posts and cast root inlays on self-etching adhesive system (LLC "Endo Press", 2020)
The effectiveness of restoration of decayed teeth with molded inlays and fiberglass posts is discussed in the article. Using scanning electron microscopy (SEM), the authors investigated the degree of microleakage at fixing posts and root inlays. A self-etching adhesive and dual-cured cement were used. At small film thickness of cement there was no gap observed. Questions of micromechanical retention were discussed. The study results allow to recommend self-etching system and dual-cure cement for fixing posts/root inlays for the root canals.